Hemorrhagic collision metastasis in a cerebral arteriovenous malformation. (25th September 2014) - Sundarakumar, Dinesh K; Marshall, Desiree A; Keene, C Dirk; Rockhill, Jason K; Margolin, Kim A; Kim, Louis J
Abstract : A 26-year-old patient with recurrent choriocarcinoma of the testis presented with headache and progressive left homonymous hemianopsia. On initial MRI a grade 4 arteriovenous malformation (AVM) was identified in the right occipital lobe, which was further characterized by catheter angiography. Continued worsening of the headache in the following days prompted a follow-up MRI, which revealed a new T2 hypointense nodule and adjacent vasogenic edema in the periphery of the AVM. A follow-up MRI showed a marked increase in the size of the nodule with intrinsic enhancement and worsening perilesional edema. Based on the imaging evolution, the nodule was diagnosed as a metastasis and the patient was started on chemotherapy and radiotherapy. One week after the MRI he developed a sudden hemorrhage within the mass requiring decompression craniectomy and resection of both AVM and tumor. The histopathology of the resected mass confirmed the diagnosis of choriocarcinoma metastasis to the AVM.